1, 5-disubstituted-1, 2, 3-triazoles counteract mitochondrial dysfunction acting on F1FO-ATPase in models of cardiovascular diseases. (January 2023) - Algieri, Cristina; Bernardini, Chiara; Marchi, Saverio; Forte, Maurizio; Tallarida, Matteo Antonio; Bianchi, Franca; La Mantia, Debora; Algieri, Vincenzo; Stanzione, Rosita; Cotugno, Maria; Costanzo, Paola; Trombetti, Fabiana; et al.
Abstract: The compromised viability and function of cardiovascular cells are rescued by small molecules of triazole derivatives (Tzs), identified as 3a and 3b, by preventing mitochondrial dysfunction. The oxidative phosphorylation improves the respiratory control rate in the presence of Tzs independently of the substrates that energize the mitochondria. The F1 FO -ATPase, the main candidate in mitochondrial permeability transition pore (mPTP) formation, is the biological target of Tzs and hydrophilic F1 domain of the enzyme is depicted as the binding region of Tzs. The protective effect of Tz molecules on isolated mitochondria was corroborated by immortalized cardiomyocytes results. Indeed, mPTP opening was attenuated in response to ionomycin. Consequently, increased mitochondrial roundness and reduction of both length and interconnections between mitochondria. In in-vitro and ex-vivo models of cardiovascular pathologies ( i.e., hypoxia-reoxygenation and hypertension) were used to evaluate the Tzs cardioprotective action. Key parameters of porcine aortic endothelial cells (pAECs) oxidative metabolism and cell viability were not affected by Tzs. However, in the presence of either 1 μM 3a or 0.5 μM 3b the impaired cell metabolism of pAECs injured by hypoxia-reoxygenation was restored to control respiratory profile. Moreover, endothelial cells isolated from SHRSP exposed to high-salt treatment rescued the Complex I activity and the endothelial capability to form vessel-like tubes and vascular function in presence of Tzs. As a result, the specific biochemical mechanism of Tzs to block Ca 2+ -activated F1 FO -ATPase protected cell viability and preserved the pAECs bioenergetic metabolism upon hypoxia-reoxygenation injury. Moreover, SHRSP improved vascular dysfunction in response to a high-salt treatment. Graphical Abstract: ga1 Highlights: The Ca 2+ -activated F1 FO -ATPase inhibition by Tzs affects the mPTP. Tzs can counteract the mPTP-related cardiovascular damage. Vascular endothelial cell metabolism is rewired by Tzs upon hypoxia-reoxygenation. Tzs are protective against endothelial dysfunction caused by high-salt exposure.